1933 - Die Gleichschaltung des politischen Katholizismus in Baden Ein Beitrag zur Geschichte der nationalsozialistischen Machtübernahme - Schmiesing, Jürgen (KIT Scientific Publishing, 2013)
This study deals with with the enforced conformity ("Gleichschaltung") of the Baden Center Party (Badische Zentrumspartei) during the process of National Socialist takeover in 1933. Based on documents in the estate of Center Party politician F. X. Schmerbeck (Karlsruhe), it provides a rare insight into the opposition`s struggle for political influence and its own internal contradictions.